Zanimivosti iz življenja lesne sove Strix aluco - Vrezec, Al (Acrocephalus, 1994)
The author presents his observations and a thorough study of the Tawny Owl Strix aluco in the village of Hrastje near Polčane from 1991 to the beginning of 1994. The observations were made possible with the aid of the owl's recorded songs or calls broadcast there, for with such method the presence andnumber of owls can be quickly ascertained in a certain area. In this way a Tawny Owl male, among other birds, was provoked which, however, reacted ratheraggressively to the recorded song. In May 1991 the author discovered a Tawny Owl's nest in a beech hole, but unfortunately it went to ruin due to a sudden and considerable fall in temperature at that time. In the following years, however, the Tawny Owl bred there successfully In 1992, 4 chicks were fledged; through the entire summer they kept together, but in late autumn theysuddenly scattered to the four winds. The author describes the bird's three dif ferent daily resting places: nest hole, man made hatchery, and chimney on the roof in the vicinity of the owl's nest hole. Most interesting was certainly the latter, for the owl was not no ticed there by other birds and thus remained undisturbed. The test, according to which the owl's song wasbroadcast in the immediate neighbourhood of the above mentioned house was interesting as well. There were a number of different birds attracted by it, but did not dis turb the owl perching on top of the chimney The studied owl was a grey variety of this species. In this region it hunts also in different sheds, stables and stalls, where it catches according to the author's belief -mostly dorm ice Glis glis, black rats Rattus rattus and house mice Mus usculus, which together with other small mammals hunted in nearby forests any vineyards represent the greater part of its die in this area.
Keywords: Birds; Strix aluco; Ecosystem; lesna sova; ornitologija; Behavior, animal; bird; ptice